The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1039/c6sm00295a
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of ordered colloidal particle monolayers at nematic liquid crystal interfaces

Abstract: We prepare two-dimensional crystalline packings of colloidal particles on surfaces of the nematic liquid crystal (NLC) 5CB, and we investigate the diffusion and vibrational phonon modes of these particles using video microscopy. Short-time particle diffusion at the air-NLC interface is well described by a Stokes-Einstein model with viscosity similar to that of 5CB. Crystal phonon modes, measured by particle displacement covariance techniques, are demonstrated to depend on the elastic constants of 5CB through i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…Similar to electrically charged particles, like-sign topological defects, in general, repel each other, while defects of opposite sign attract. However, this can be additionally affected by the geometry and surface properties of * anupams@ethz.ch the environment [17,18], and the presence of an external stimulus [19][20][21][22][23]. Emergence of topological defects in a field, and the resulting interactions between them, have been well characterized [24].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to electrically charged particles, like-sign topological defects, in general, repel each other, while defects of opposite sign attract. However, this can be additionally affected by the geometry and surface properties of * anupams@ethz.ch the environment [17,18], and the presence of an external stimulus [19][20][21][22][23]. Emergence of topological defects in a field, and the resulting interactions between them, have been well characterized [24].…”
Section: Introductionmentioning
confidence: 99%
“…Problem B concerns the drag force on a particle straddling an Iso-N interface. As mentioned in the introduction, a few experiments have touched upon this topic [24,28,29] but no prior theoretical or computational work seems to have been reported so far. Fig.…”
Section: Problem B: Drag Forcementioning
confidence: 99%
“…At the single particle level, Jeridi et al [25,26] reported capillary-induced giant elastic dipoles in thin nematic wetting films, whereas the influence of interfacial curvature was addressed by Gharbi et al [27] by placing particles on NLC shells. More dynamical aspects such as the Brownian diffusion of micro-and nano-particles at the nematic-aqueous phase interface were first investigated by Abras et al [28], whereas the vibrational phonon modes of 2D crystalline packings of particles at the air-NLC interface were discussed by Wei et al [29].…”
Section: Introductionmentioning
confidence: 99%
“…In simple fluids, the capillary forces compete mostly with electrostatic interactions . When inclusions are attached at complex fluid interfaces such as a bilayer membrane ,,, or a liquid crystal interface, other long-range interactions related to bulk distortions of the surrounding fluid appear. For instance, a nematic liquid crystal phase is characterized by a preferred orientationthe director n­(r )of its long rigid molecules.…”
Section: Introductionmentioning
confidence: 99%